Comparative analysis of different grades of gaharu using NMR- and GCMS- based metabolomics approach - Ismail, Siti Nazirah (2015)
Gaharu, also referred to as agarwood, kalambak, aloeswood or eaglewood, is the resinous heartwood of infected Aquilaria sp. where infection may occur due to the attack by fungi, insects or other external injuries. In gaharu trade, gaharu wood is graded by experts using organoleptic methods because there is no other scientific method to determine the grades. Normally they are graded according to observable traits such as odor upon burning, color and wood density which reflects the resin content of the woods. Basically price of gaharu follow the grades with highest grade being the most expensive. The aim of this study was to carry out a comparative analysis of the different grades of gaharu by making use of their multicomponent metabolite profiles in order to ascertain whether they can be used to differentiate between one grade to another. To achieve this aim, 1H Nuclear Magnetic Resonance (1H NMR) and Gas Chromatography Mass Spectrometry Spectrometry (GCMS) combined with multivariate data analysis were used to analyze the variation between the metabolite profiles of the different grades of gaharu samples. Gaharu woods finely milled into fine powder, then extracted by using distilled methanol and dried using Genevac. The gaharu crudes were proceed for 1H NMR analysis, by dilution with deuterated methanol. Visual inspection on 1H-NMR gaharu spectra shows that the grades have similar profile but different concentration of various constituents. Major constituents identified are aromatics (δ6.0-7.5), sugar and glycosides (δ2.5-5.0), fatty acids/aliphatics (δ0.5-2.0) and aldehydic compound (δ9.32). However, since the difference among the grades is not clear from visual analysis, the analysis were carried out using multivariate analysis. Principal Component Analysis (PCA) model overview of 4 batches of all grades of gaharu does not provide useful information, thus further analysis was carried out on consistency of individual grade for each batch of gaharu to see which batch and grades are suitable as class model. According to their chemical constituents, the grades reclassified into 5 new groups (A, B, C, D and E). Group A more significant in sugar constituents (4.24-4.28 ppm) and possibly terpenoids (1.12, 1.16, 1.32, and 2.04 ppm), while group C and E are different from the rest due to higher aliphatics (3.0, 4.0, 4.52 and 7.2 ppm). On the other hand, group B and D different from other grades by possibly terpenoidal constituents as well (0.80, 0.84, 0.88, 1.24, and 1.28 ppm). In order to identify the chemical markers that contributed to the differentiation of the gaharu, NMR experiments, comprising 1D and 2D as well as J-resolve, were carried out on selected fractions of the gaharu extract. The highest grade gaharu was selected for the fractionation via solid phase extraction (SPE). An ethylphenylchromone type compound was identified as on of the major constituents in the 50% SPE fractions of gaharu grade 1. Further analysis by Liquid Chromatography-Mass Spectrometry (LCMS) resulted in the identification of 6-hydroxyethylphenylchromone and dihydroxy-2-[(2-phenyl)-ethyl]chromones, two fatty acids which were (9Z,12Z)-15,16-dihydroxyoctadeca-9,12-octadecadienoic acid and (11Z,14Z)-17,18-dihydroxyicosa-11,14-dienoic acid as well as sesquiterpenes which were aquilarone B, aquilarone D or E, and aquilarone F. Gaharu smoke was captured on the glass fiber filter using a simple lab setup comprising an incense burner, connected to a glass tube containing the glass fiber. To ensure absorption of smoke, the setup was linked to a vacuum line. The fiber filter containing smoke were directly analyzed by headspace GCMS analysis. Volatile constituents detected in the gaharu smoke included aldehydes (benzaldehyde and cuminaldehyde) and aromatics (toluene, 2-methylanisole, p-cresol, creosol, anisole, o-cresol and acetophenone). Other constituents detected were furfuryl alcohol and benzylideneacetone. Orthogonal Partial Least Square-Discriminant Analysis (OPLS-DA) of the gaharu smoke profiles can be differentiated into a terpene rich and a chromone rich groups. The terpene rich group consisted of the higher grades gaharu samples, while the chromone rich group consisted of the lower grade samples. Further treatment of the variables using Variable Importance in Projection (VIP) for independent variables resulted in the identification of p-cresol (m/z 107.05), 2-methylanisole (m/z 122.10), toluene (m/z 91.05) and p-anisaldehyde (m/z 135.10), as some of the discriminating chemical markers present in the high grade gaharu smoke. Meanwhile furfuryl alcohol (m/z 98.05) and 5-methylfurfural (m/z 110.05) were some of the markers present in lower grades. On the overall, this study has shown that spectrometry-based metabolomics could offer a better approach in grading of gaharu qualities.